Transcriptome Analysis Reveals the Role of Phytohormones in the Distant Hybridization of Peony Embryo Abortion - Dan He; Haonan Guo; Songlin He; Mingxing Zhang; Yihong Chang; Zheng Wang; Yiping Liu (Horticulturae, 2023)
Peonies are significant ornamental plants that are primarily propagated through distant cross-breeding to create new varieties. However, hybrid failure is a critical issue that impedes the advancement of breeding. Numerous studies have demonstrated that endogenous hormones in the seed embryo constitute a significant factor in embryo failure. Nevertheless, it is still unknown how plant hormones control the development of peony embryos at the molecular level. In this study, we characterized the endogenous hormone levels in peony seeds of hybrid-aborted, hybrid-normal, and self-crossing normal after 26 days of pollination (DAP). Our findings show that the hybrid-aborted embryos had significantly higher amounts of ABA, IAA, and GA. In addition, the ratio of GA+IAA/ABA was lower than that of the hybrid-normal seeds and higher than that of the self-crossing normal seeds. To further investigate the mechanism of hormone control on peony embryo development, we conducted a transcriptome sequencing analysis of the three seed types. Results revealed that differentially expressed genes involved in phytohormone metabolism and signal transduction significantly enriched the aborted embryos. Furthermore, we examined the expression levels of six hormones in different seeds and used the Gene Common Expression Trend analysis to analyze genes highly correlated with phytohormone in the KEGG pathway. We used protein interaction networks to explore the interactions between proteins in the hormone pathway in aborted embryos. Then we identified key genes and transcription factors (TFs) such as Abscisic acid-insensitive 5 (ABI5), Auxin Response Factor 5 (ARF5), Gibberellin Insensitive Dwarf 1 (GID1), Arabidopsis Response Regulator4 (ARR4), Jasmonate-zim-domain protein 1 (JAZ1), Brassinazole-resistant 1 (BZR1), etc., whose functions require further investigation. Our findings establish a foundation for the metabolic regulation of peony hybrid embryo abortion via networks regulating phytohormone signaling. However, further research is needed to determine the exact mechanisms by which hormones regulate peony embryo development and to explore new methods for improving the success rate of hybridization.